Folklore text as a material for the development of creative thinking of undergraduate students - Astafyeva, Yuliya; Немченко, Н. (Pedagogy and Psychology, 2022)
Folklore text as a material for the development of creative thinking of undergraduate students This article dwells upon the development of creativity in undergraduate language students. The authors specify that a fairy tale text can serve as the material on the basis of which the process of creative and critical thinking development can be built. To work on the theoretical and methodological basis of the study, the authors pay much attention to the research of scientists who have contributed to the study of creativity. In the article the authors narrate about different forms of organization of actually creative types of speech activity. The authors focus the readers’ attention on the fact that to build a methodological model of exercises and tasks that would develop creative skills on the basis of fairy tale texts, the Dublin teaching methodology is offered, which promotes both the development of foreign language spoken and written speech of students, and their creative thinking. In addition, the authors offer readers to get acquainted with this model on the basis of examples of the developed system of practical assignments for working on the text of a fairy tale.